1998
DOI: 10.1002/(sici)1098-2264(199805)22:1<50::aid-gcc7>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization analysis of sporadic neuroendocrine tumors of the digestive system

Abstract: Little information is available on the molecular mechanisms underlying neuroendocrine tumorigenesis. To obtain an overview of the genomic imbalances characterizing these tumors, we studied 20 benign or malignant sporadic endocrine gastroenteropancreatic tumors by comparative genomic hybridization. Chromosomal imbalances were found in all tumors. Gains of chromosomal material were more frequent than losses. The most frequent gains were of chromosomes and chromosome arms 5 (55%), 14 (55%), 17q (55%), and 7 (50%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
59
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 24 publications
16
59
1
Order By: Relevance
“…Overrepresentations of chromosome 5 are also observed in other cancers, including adrenocortical 30 and gastrointestinal endocrine tumors. 21 Because the latter study reported frequent associations of gains of chromosome 5 and 7 and, to a lesser extent, 12, and our CGH data could demonstrate 5q gains already present in three benign insulinomas, the search for a possible oncogene on chromosome 5q in EPTs seems to be justified. Two regions on 7q were mostly involved, ie, 7q11.2-q22 and 7q31.3-q32, which may harbor putative oncogenes, eg, MET at 7q31.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overrepresentations of chromosome 5 are also observed in other cancers, including adrenocortical 30 and gastrointestinal endocrine tumors. 21 Because the latter study reported frequent associations of gains of chromosome 5 and 7 and, to a lesser extent, 12, and our CGH data could demonstrate 5q gains already present in three benign insulinomas, the search for a possible oncogene on chromosome 5q in EPTs seems to be justified. Two regions on 7q were mostly involved, ie, 7q11.2-q22 and 7q31.3-q32, which may harbor putative oncogenes, eg, MET at 7q31.…”
Section: Discussionsupporting
confidence: 85%
“…2 Although approximately 50% of sporadic EPTs show allelic deletions of the MEN1 gene, the mutation rate was 2 to 3 times lower in frequency, pointing to the existence of yet another TSG more telo-meric of the MEN1 gene. 5,21,22 Consistent with this hypothesis, we found losses of 11q in 36% of EPTs, with the smallest CRI at 11q13-q22. In addition, we found losses of 11p (CRI: 11p13-p14) in 30% of cases, which is in accordance with other data 10 and might point to the Wilms' tumor gene WT1 on 11p13 as a potential candidate TSG.…”
Section: Discussionmentioning
confidence: 99%
“…Using microsatellite markers, chromosome-based comparative genomic hybridization (CGH) and single nucleotide polymorphism (SNP) analysis, recurrent copy number alterations (CNAs) have been identified. The most common CNA is loss of chromosome 18 (Terris et al 1998, Zhao et al 2000, Kytölä et al 2001, Löllgen et al 2001, Tönnies et al 2001, Stancu et al 2003, Wang et al 2005, Kim do et al 2008, Kulke et al 2008. Other recurrent CNAs include losses involving chromosomes 9, 11q and/or 16q, and gains involving chromosomes 4, 5, 7, 14 and/or 20.…”
Section: Introductionmentioning
confidence: 51%
“…Loss of 9p, 11q, 16q, and 18 in all but three tumors used in this study has been reported in our previous study using microsatellite markers , and was similar to LOH regions determined by SNP allelotyping reported in the current study. Previous studies have reported loss of 9p, 11q, 16q, and 18, and gains of chromosomal arms 4p, 17q, 19q, and 4p in WDNTs from lung and gastrointestinal tract by microsatellite analysis and comparative genomic hybridization (Terris et al, 1998;Kytö lä et al, 2001;Lö llgen et al, 2001;Tö nnies et al, 2001;Wang et al, 2005). Chromosomal aberrations were more common in PETs using the same methodology compared to WDNTs from lung and gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 90%